2014
DOI: 10.1242/jeb.101683
|View full text |Cite
|
Sign up to set email alerts
|

Non-visual numerical discrimination in a blind cavefish (Phreatichthys andruzzii)

Abstract: Over a decade of comparative studies, researchers have found that rudimentary numerical abilities are widespread among vertebrates. While experiments in mammals and birds have employed a variety of stimuli (visual, auditory and tactile), all fish studies involved visual stimuli and it is unknown whether fish can process numbers in other sensory modalities. To fill this gap, we studied numerical abilities in Phreatichthys andruzzii, a blind cave-dwelling species that evolved in the phreatic layer of the Somalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Ever since Koehler and his co-workers explored the numerical capabilities of birds [31], corvids have been known to show some level of quantity discrimination [32], and they use quantity rules to direct behaviour [33]. Jungle crows have been trained on relative numerosity discriminations to always choose the larger of two sets of (3)(4)(5)(6)(7)(8) visual shapes [34]. Relative quantity judgements are also observable without training, as crows and jackdaws [20] spontaneously selected the larger of two food quantities as long as one of the sets contained fewer than five objects [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since Koehler and his co-workers explored the numerical capabilities of birds [31], corvids have been known to show some level of quantity discrimination [32], and they use quantity rules to direct behaviour [33]. Jungle crows have been trained on relative numerosity discriminations to always choose the larger of two sets of (3)(4)(5)(6)(7)(8) visual shapes [34]. Relative quantity judgements are also observable without training, as crows and jackdaws [20] spontaneously selected the larger of two food quantities as long as one of the sets contained fewer than five objects [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our behavioral experiments were not based on a simple visual comparison task as was conducted with other fish [1013,15]. Indeed, the two values to be compared, the number of food pellets, are never present simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that in various species such as mosquitofish or angelfish, an individual will spontaneously join the bigger of two shoals in an attempt to avoid predators, but only when the difference in the number of individuals is significant and enables an easy discrimination [1012]. In addition, other fish can also discriminate small quantities of objects [13,14], recognize the door with the correct number of symbols [15] or encode ordinal information [16]. They are able to perform above chance even when not given access to all the items together [17] or when they are deprived of the sense of sight [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the possibility exists that vertebrates share a core numerical system inherited by a common ancestor (e.g., [33]). For instance, a recent study found that even blind cavefish that lived in the darkness of Somalia caves in the total absence of predators for approximately two million years display numerical abilities partially similar to those described in other fish species [34]. Similarly, horses might exhibit some rudimentary numerical abilities irrespective to the ecological pressures received across evolution.…”
Section: Introductionmentioning
confidence: 91%